2019
DOI: 10.3390/jcm8081105
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Level of Blood MicroRNA-133b in Men with Opioid Use Disorder on Methadone Maintenance Therapy

Abstract: Although previous animal studies have indicated that certain micro ribonucleic acids (microRNAs) play a part in the pathway of opioid addiction, whether such findings extend to human models is yet unknown. This study aims to investigate the important microRNA expressions in patients with opioid use disorder (OUD) on methadone maintenance treatment (MMT) compared to healthy controls and analyze the correlation between microRNAs and opioid characteristics among the patients. We recruited 50 patients and 25 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In this study, a significant increase in miR-206 expression is observed, which is consistent with the analysis of Gu W-J et al [ 12 ], who stated steadily increased Let-7b-5p, miR-206, and miR-486-5p levels in heroin drug addicts. Similarly, Hsu et al [ 29 ] reported miR-206 and miR-210 overexpression in 50 opioid use disorder (OUD) patients who were receiving methionine medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a significant increase in miR-206 expression is observed, which is consistent with the analysis of Gu W-J et al [ 12 ], who stated steadily increased Let-7b-5p, miR-206, and miR-486-5p levels in heroin drug addicts. Similarly, Hsu et al [ 29 ] reported miR-206 and miR-210 overexpression in 50 opioid use disorder (OUD) patients who were receiving methionine medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, researchers have looked at how miRNA are changed in response to drugs. One example from clinical literature is that specific miRNA are differentially expressed in patients with opioid use disorder compared to healthy controls ( Hsu et al, 2019 ). Here we suggest that exposure to stress in adolescence (in the absence of any drug exposure) also changes miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on miR-133b have found correlations to opioids and pain pathways. For example, miR-133b levels in blood were significantly decreased in men on methadone maintenance therapy who had a history of OUD compared to healthy controls ( Hsu and Tsai., 2019 ). miR-133b may also be involved in pain pathways of post-stroke rat models, as it was significantly downregulated in rats experiencing intense post-stroke pain.…”
Section: Mir-133bmentioning
confidence: 99%